Selecting a Name for Your 4-H Club - Keith G. Diem; Marilyn N. Norman; Joy C. Jordan; Lindsey McConnell (EDIS)
Each 4-H club is a unique group of individuals who work together toward common goals. A club name should reflect the purpose(s) of the club, often relating to the project(s) the club participates in, or the geographic area where members live or the club meets. One of the first ways to develop a sense of belonging and youth engagement is allowing all of the members to participate in selecting a name for the club. Information in this sheet may help you guide the members in making a wise name choice. This 2-page fact sheet was written by Keith G. Diem, Marilyn N. Norman, Joy C. Jordan, and Lindsey McConnell, and published by the UF Department of 4-H Youth Development, July 2014.